Tight Binding of Plasmid DNA With Self-Assembled Tetramethylguanidinium Conjugated Polyethylenimine Suppresses Transfection Efficiency - Yadav, Santosh; Sharma, Ashwani Kumar; Kumar, Pradeep (Frontiers in Nanotechnology, 2021)
Here, we have demonstrated that on modification of linear polyethyleneimine (lPEI, LP) with amphiphilic 3-bromopropyltetramethylguanidinium (PTMG) linker, the transfection efficiency exhibited by the modified polymers decreased while cell viability improved. A series of LP-PTMG polymers was synthesized by reaction of varying amounts of 3-bromopropyltetramethylguanidinium linker on lPEI (25 kDa). These modified polymers interacted efficiently with pDNA and formed stable complexes with pDNA as shown by dynamic light scattering analysis. The size of the complexes in the series LP-PTMG/pDNA was found to be in the range of 178 nm to 205 nm. The interaction of modified polymers with plasmid DNA was stronger than linear PEI as evidenced by heparin release assay which showd ~83% pDNA release from LP-PTMG-3/pDNA complexes in comparison to ~95% in lPEI/pDNA complexes on treatment with same amount of heparin suggesting the formation of self-assembled structures in modified polymers. In vitro transfection experiments in HeLa and CHO cell lines showed a decrease in transfection efficiency of modified polymers which might be due to strong binding of modified polymers with pDNA due to accumulation of charge on the surface. These results showed the importance of optimum binding of polymer and DNA to form polyplexes as well as release of DNA from the polyplex.